Genetic Transformation of Coleus blumei Benth. Using Agrobacterium - Nataša Bauer (Food Technology and Biotechnology, 2002)
Efficiency in transformation of three hybrids of Coleus blumei using wild and mutant strains of Agrobacterium sp. was evaluated. Successful transformation depended on specific bacterial strain-plant genotype combination and co-cultivation treatment. The wild type B6S3 of the bacterial strains employed gave the maximum efficiency. Strains C58C1(pArA4abc), GV3101(pGV2215), 8196 and A281 were also effective. Among several co-cultivation conditions tested, the most efficient treatment was as follows: excised leaf explants were incubated immeadiately in bacterial suspension for 5 min and were co-cultured with Nicotiana tabacum crown gall callus for two days. Plant hormone autotrophy, PCR analyses and hybridization analysis confirmed genetic transformation of the cultures. Sixteen different transgenic callus and cell cultures were maintained for more than four years in the absence of exogenous growth regulators and antibiotics without deterioration in the growth rate.